Prayers to the White Blood Datuk in the Chinese Ethnic Faith in Medan Kesawan - Jihan Fahira; Desi Herawati; Dumel Awiyah Br Harahap; Epridasari Batubara; Saputri (al-Afkar, Journal For Islamic Studies, 2025)
The Sembahyang Datuk Darah Putih ritual is a significant practice among the Tionghoa ethnic community in Medan Kesawan, reflecting a unique syncretism between Chinese religious beliefs and local Malay spiritual traditions. This study aims to explore the historical and cultural significance of this ritual, the religious syncretism involved, and the factors contributing to its preservation. Employing a qualitative research method with an ethnographic approach, data were collected through in-depth interviews, participatory observations, and document analysis. The findings reveal that the veneration of Datuk Darah Putih is rooted in the historical interactions between Chinese immigrants and local Malay communities, symbolizing respect, gratitude, and a form of spiritual protection. The ritual has evolved over generations, adapting to contemporary socio-cultural changes while maintaining its core religious essence. The study also identifies challenges in sustaining the tradition, including modernization and diminishing interest among younger generations. The research concludes that Sembahyang Datuk Darah Putih serves as a cultural bridge between the Tionghoa and Malay communities, reinforcing interethnic harmony and religious tolerance. Further studies are recommended to examine the broader impact of such syncretic practices on multicultural societies.